Interlaboratory study on Sb2S3 interplay between structure, dielectric function, and amorphous-to-crystalline phase change for photonics - Gutiérrez, Yael; Ovvyan, Anna P.; Santos, Gonzalo; Juan, Dilson; Rosales, Saul A.; Junquera, Javier; García-Fernández, Pablo; Dicorato, Stefano; Giangregorio, Maria M.; Dilonardo, Elena; Palumbo, Fabio; Modreanu, Mircea; et al. (iScience, 2022)
Antimony sulfide, Sb2S3, is interesting as the phase-change material for applications requiring high transmission from the visible to telecom wavelengths, with its band gap tunable from 2.2 to 1.6 eV, depending on the amorphous and crystalline phase. Here we present results from an interlaboratory study on the interplay between the structural change and resulting optical contrast during the amorphous-to-crystalline transformation triggered both thermally and optically. By statistical analysis of Raman and ellipsometric spectroscopic data, we have identified two regimes of crystallization, namely 250°C ≤ T < 300°C, resulting in Type-I spherulitic crystallization yielding an optical contrast Δn ∼ 0.4, and 300 ≤ T < 350°C, yielding Type-II crystallization bended spherulitic structure with different dielectric function and optical contrast Δn ∼ 0.2 below 1.5 eV. Based on our findings, applications of on-chip reconfigurable nanophotonic phase modulators and of a reconfigurable high-refractive-index core/phase-change shell nanoantenna are designed and proposed.
Die Zahlen 2 und 3 im Titel sind hochgestellt
Gesehen am 13.08.2025